Contributions of Maltina Dance Reality Show to Dance Practice in Nigeria - Jacob, Oluwafemi A. (NIU Journal of Humanities; Vol 8 No 4 (2023): NIU Journal of Humanities, Vol. 8 No. 4, December 2023, 2024)
Dance involves the totality and living experience of man from the prehistoric times till date. It was part of all his daily activities such as his work, communication and even in his worship of the gods and ancestors (Nigeria inclusive). To this extent, the Nigeria dance practice has developed greatly even in the face of multi ethnicity as it has given birth to various indigenous dances. These indigenous dances have also been the raw materials to every form of contemporary dances that has emerged over the years. Diverse platforms have also surfaced to help sustain Nigerian dances such as National Arts Festival (NAFEST), Nigeria University Theatre Arts Festival (NUTAF) and the trend of dance reality shows that has been the order of the day within recent times in Nigeria. An undoubted reality television show that has done greatly in the sustainability of Nigerian dances is Maltina Family Dance All Reality Television Show. The functionalist theory of dance is used to unveil the reality show which has been able to adjust to bridge the gap between the prehistoric era and the contemporary or modern era by using technological advances to keep the dance practice in shape. This research will examine Maltina Family Dance All Reality Television Show within the context of dance praxis and the immense contributions to dance practice and sustainability in Nigeria with a view to how it has put Nigeria indigenous dances to practice since the inception till date in the face of globalization and industrialization. It will conclude that the dance reality show has provided dance practitioners both with dance repertoires and engagement with diverse indigenous dances as well as rewards both as individuals and as professionals. Keywords: Dance, Dance Reality Show, Dance Art / Practice, Maltina Dance All Family Reality Television Show.